Critical Thinking Profile of Senior High School Students in terms of Argumentation-Based Learning - Rizki Nur Fadillah; Budi Jatmiko; Wahono Widodo (Indonesia Approach Education, 2022)
This study aims to describe the profile of critical thinking based on argumentation learning in senior high school. This study used a quantitative descriptive study with a subject of 30 students. Subjects were asked to choose the correct answer based on the questionnaire and questions about critical thinking. The results from the questionnaire showed that students' critical thinking skills are 43% in the low category; 47% in the medium category, and 10% students in the high category. As evidenced by the average test results of critical thinking skills, the results obtained are 57.5 in the low category. In the indicator of formulating problems, the results obtained are 57.5 with low critical thinking categories; indicators provide arguments and analyze results 50 with low critical thinking categories; and the result deduction indicator is 60 with medium critical thinking category.Therefore, it can be recommended that the first step to improving critical thinking skills is to conduct argumentation-based learning so that students can convey arguments in physics learning and students' critical thinking skills can increase, so that it's expected to produce competent students according to 21st-century learning.